Targets and management of hypertension in heart failure: focusing on the stages of heart failure - Miao, Huanhuan; Zou, Changhong; Yang, Shijie; Chia, Yook Chin *; Huynh, Minh Van; Sogunuru, Guru Prasad; Tay, Jam Chin; Wang, Tzung-Dau; Kario, Kazuomi; Zhang, Yuqing (Wiley, 2022)
Hypertension is highly prevalent worldwide and is the major risk factor for heart failure (HF). More than half of the patients with HF in Asia suffer from hypertension. According to the 2022 American Heart Association/American College of Cardiology/Heart Failure Society of America HF guideline, there are four stages of HF, including at risk for HF (stage A), pre-HF (stage B), symptomatic HF (stage C), and advanced HF (stage D). Given the high prevalence of hypertension as well as HF and the stronger association between hypertension and cardiovascular diseases in Asians compared to the west, measures to prevent and alleviate the progression to clinical HF, especially controlling the blood pressure (BP), are of priority for Asian populations. After reviewing evidence-based studies, we propose a BP target of less than 130/80 mmHg for patients at stages A, B, and C. However, relatively higher BP may represent an opportunity to maximize guideline-directed medical therapy (GDMT), which could potentially result in a better prognosis for patients at stage D. Traditional antihypertensive drugs are the cornerstones for the management of hypertension at stages A and B. Notably, calcium channel blockers (CCBs) are inferior to other drug classes for the preventing of HF, whereas diuretics are superior to others. For patients at stage C, GDMT is essential which also helps the control of BP. In particular, sodium-glucose cotransporter-2 (SGLT2) inhibitors are newer therapies recommended for the treatment of HF and presumably even in hypertension to prevent HF. Regarding patients at stage D, GDMT is also recommended if tolerable and measures should be taken to improve hemodynamics.